Barriers and opportunities in cross-border electricity trading for Bhutan - Choden, Tenzin; Weerakorn Ongsakul; Singh, Jai Govind; Ekbordin Winijkul; Asian Development Bank-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Bhutan, gifted with huge potential for the development of hydroelectricity, that significantly surpass its domestic needs and gaining its importance on export surplus of power among Bangladesh, Bhutan, India and Nepal (BBIN) region. However, Bhutan face a challenging task to provide adequate, quality and affordable power in sustainable manner. To address this gap a "bottom up" approach study involving stakeholders' perception is proposed. This is based on the Strength, Weakness, Opportunity and Threat (SWOT) linked with Analytical Hierarchy Processes (ARP) where a pairwise comparison and ranking of SWOT factors is performed and finally a strategy is developed based on the TOWS matrix. The method is applied to examine the opportunities and barriers in cross-border trading of electricity from the Bhutan context, considering the current bilateral trading with Bhutan - India and envisioning the trilateral trading between Bhutan - Bangladesh, India as transit. The outcome of Bhutanese experts in energy perceived that for both the electricity trading, the weaknesses category needs be emphasized more to expand huge volume of trade in electricity. While the most suitable strategy to overcome the internal weaknesses are (i) to emphasize in-house capacity building and (ii) establishing a multi-country investment and encouraging PPP in CBET projects. The results of these findings will help the country to get some insight in terms of the critical external and internal barriers that may hinder the progress of regional electricity trading.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M. Eng.) - Asian Institute of Technology, 2019
Keywords: Renewable energy sources -- Bhutan; Electric power production -- Bhutan -- Marketing; Electric power distribution -- Bhutan